2019
DOI: 10.1002/aoc.4946
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti‐proliferative and in silico docking studies of heteroleptic copper(II) complexes of pyridazine‐based ligands and ciprofloxacin

Abstract: Three heteroleptic copper(II) complexes of the type [Cu(L1–3)(cf)(ClO4)] (1–3), where cf = ciprofloxacin, have been synthesized using pyridazine‐based ligands 3‐chloro‐6‐(salicylidenehydrazinyl)pyridazine (HL1), 3‐chloro‐6‐(4‐diethylaminosalicylidenehydrazinyl)pyridazine (HL2) and 3‐chloro‐6‐(5‐bromosalicylidenehydrazinyl)pyridazine (HL3). Electronic spectral data and magnetic moment values suggest octahedral geometry for the synthesized copper(II) complexes. Electrochemical data of the copper(II) complexes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Two bands in the range 519-520 and 410-460 cm −1 were assigned to ν(M-O) and ν(M-N), respectively. [39,40] The IR spectra of the ligand and its metal complexes are shown in Figure S1. Finally, it is concluded from the IR spectra of all prepared compounds that the azo-dye ligand coordinated to the metal ions through four sites-two nitrogen sites of the azo groups and two oxygen sites by deprotonation of the phenolic groups.…”
Section: Ir Spectramentioning
confidence: 99%
“…Two bands in the range 519-520 and 410-460 cm −1 were assigned to ν(M-O) and ν(M-N), respectively. [39,40] The IR spectra of the ligand and its metal complexes are shown in Figure S1. Finally, it is concluded from the IR spectra of all prepared compounds that the azo-dye ligand coordinated to the metal ions through four sites-two nitrogen sites of the azo groups and two oxygen sites by deprotonation of the phenolic groups.…”
Section: Ir Spectramentioning
confidence: 99%
“…The inhibitory properties of copper(II) complexes on breast cancer cell proliferation were detected by MTT assay. The experiments showed that the complexes exhibited a significant proliferation inhibition effect on the human breast cancer cell line (MCF-7), and the cell viability was affected by the complexes [ 67 ]. The number of breast cancer cells decreased with increasing copper complex concentration.…”
Section: Application Of Novel Copper Complexes In Tumor Therapymentioning
confidence: 99%
“…In this context, heteroleptic transition metal complexes, which contain two or more different ligands, have gained particular attention as an important category of transition metal complexes [23][24][25][26][27][28] because of the stepwise dissociation during the formation of metal-DNA complexes, which enhances the cellular uptake and consequently the anticancer activity. [29,30] The azabicyclo[3.2.1]octane moiety composes the core structure of various biologically active compounds with antiproliferative, antimicrobial, analgesic, and antiinflammatory effects that are occasionally exploited as drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, heteroleptic transition metal complexes, which contain two or more different ligands, have gained particular attention as an important category of transition metal complexes [ 23–28 ] because of the stepwise dissociation during the formation of metal–DNA complexes, which enhances the cellular uptake and consequently the anticancer activity. [ 29,30 ]…”
Section: Introductionmentioning
confidence: 99%